AN ANALYSIS OF CULTURAL MEANING RELATED TO LEXICONS IN SATYENG BERATI DANCE - Setiawan, Kadek Feri (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2023)
Satyeng Berati dance is a traditional dance from Bali with many lexicons to identify and document. But over time, several lexicons are rarely used when doing dance practice. It has the possibility of language extinction because the number of speakers of that language has decreased. The purpose of this study is to document the lexicons in the Satyeng Berati dance, especially the cultural meanings of the lexicons in movement. This study is designed in the form of descriptive qualitative research. Data collection is done through observation and interviews. Based on the results of the study, it was found that there were thirty-one lexicons in the Satyeng Berati dance movements. The lexicons are divided into six, namely, the lexicon on eye movements (four lexicons), neck movements (one lexicon), body movements (twelve lexicons), hand movements (seven lexicons), finger movements (two lexicons), and foot movements (five lexicons). The thirty-one movements are nyeledet kanan, nyeledet kiri, ngelier kanan, ngelier kiri, ngegenjet leher, ngelung bulan kanan, ngelung bulan kiri, ngotag pala, ngeseh, ngelo, sleag-sleog kanan, sleag-sleog kiri, agem kanan, agem kiri, ngegol kanan, ngegol kiri, teisik, nagastru, luk nerudut, nabdab petitis, mentang laras, nyalud, ngukel, luk ngelimat, jeriring, ulap-ulap, gandang arep, milpil, nyeregseg kanan, nyeregseg kiri, and ngelikas. These lexicons have their cultural meaning, which is certainly different from other traditional dances. The documentation activity on the lexicon in the Satyeng Berati dance is one of the efforts to preserve the local language to avoid language death.